Public policy interventions for grassroots innovations: are we getting it right? - Ng, Boon Kwee; Mohamad, Zeeda Fatimah; Chandran, V.G.R.; Mohamad Noor, Nur Hanis (Taylor & Francis, 2019)
This paper examines the socio-technical elements of Grassroots Innovations (GRIs) cases in Malaysia and draws lessons for public policy intervention by accounting for the contextual nature of the GRIs. Our findings on the four successful Malaysian rural GRIs indicate the following. First, carefully formulated level-specific policy instruments are needed to facilitate the smooth transition of the various stages of GRIs. Second, given the heterogeneity nature of GRIs, policymakers should avoid generalized, oversimplified and one-fit policy approaches. In turn, public policy intervention should be flexible and clearly suited to the aspiration of the founders and their missions. More importantly, attempts to commercialize, similar to the business-oriented innovation policy and in the name of creating value defeats the purpose of GRIs thus jeopardizing the true value of GRIs. Instead, the evidences suggest that strengthening the stakeholder-innovator partnership in co-developing and co-delivering adds value to the grassroots innovators and society at large. It also has larger benefits of application in providing greater social benefits especially in solving communal problems. © 2019, © KOSIME, ASIALICS, STEPI 2019.